2010
DOI: 10.1016/j.molimm.2009.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial P2Y2 receptor regulates LPS-induced neutrophil transendothelial migration in vitro

Abstract: Previous studies showed that P2 receptors are involved in neutrophil migration via stimulation of chemokine release and by facilitating chemoattractant gradient sensing. Here, we have investigated whether these receptors are involved in LPS-induced neutrophil transendothelial migration (TEM) using a Boyden chamber where neutrophils migrated through a layer of lipopolysaccharide (LPS)-stimulated human umbilical vein endothelial cells (HUVECs). In line with a role of P2 receptors, neutrophil TEM was inhibited by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 35 publications
2
33
0
Order By: Relevance
“…Since both P2Y 2 Rmediated transactivation of growth factor receptors and integrins contribute to cell migration [21,24,91], it is intriguing to postulate that FLNa binding to the SH3-binding domains of the P2Y 2 R links nucleotide-induced EGFR transactivation to the RGD-dependent integrin signaling pathway that regulates cytoskeletal rearrangements required to increase cell motility. In other studies, P2Y 2 R-mediated monocyte diapedesis (i.e., transendothelial migration) has been shown to occur by disruption of intercellular adherens junctions, suggesting that cytoskeletal rearrangements promoted by the P2Y 2 R also can affect cell polarization [89,93,95,[101][102][103]. Therefore, these data suggest a mechanism whereby the tropism of monocytic cells (e.g., microglia) into damaged areas of the CNS can be induced by activation of P2Y 2 Rs.…”
Section: P2y 2 Receptor Signaling Pathwaysmentioning
confidence: 51%
See 4 more Smart Citations
“…Since both P2Y 2 Rmediated transactivation of growth factor receptors and integrins contribute to cell migration [21,24,91], it is intriguing to postulate that FLNa binding to the SH3-binding domains of the P2Y 2 R links nucleotide-induced EGFR transactivation to the RGD-dependent integrin signaling pathway that regulates cytoskeletal rearrangements required to increase cell motility. In other studies, P2Y 2 R-mediated monocyte diapedesis (i.e., transendothelial migration) has been shown to occur by disruption of intercellular adherens junctions, suggesting that cytoskeletal rearrangements promoted by the P2Y 2 R also can affect cell polarization [89,93,95,[101][102][103]. Therefore, these data suggest a mechanism whereby the tropism of monocytic cells (e.g., microglia) into damaged areas of the CNS can be induced by activation of P2Y 2 Rs.…”
Section: P2y 2 Receptor Signaling Pathwaysmentioning
confidence: 51%
“…However, mechanisms by which endothelial cells promote leukocyte diapedesis are less clear. In a recent in vitro diapedesis study, expression of the endothelial P2Y 2 R was found to be important for the transendothelial migration of neutrophils toward lipopolysaccharide (LPS), a chemoattractive component of gramnegative bacteria [102]. This study also demonstrated that WT and P2Y 2 R −/− mouse primary microglial cells were treated with oAβ (1 μM), incubated for 24 h, and supernatants were collected and analyzed for TNF-α and IL-1β by ELISA.…”
Section: Proinflammatory P2y 2 R Functions In Endotheliummentioning
confidence: 69%
See 3 more Smart Citations